Clinical characteristics of patients with atrial fibrillation at a tertiary care hospital in the central region of Saudi Arabia - Salih A Bin Salih; Mohammed S Showlag; Mohammed A Al-Qahtani; Ahmad Taha; Muhammad Yousuf; Mohammed Abdullah (Wolters Kluwer Medknow Publications, 2011)
Objective: To report on the clinical presentation, etiology, and laboratory features of acute and chronic atrial fibrillation (AF) in a tertiary hospital in Riyadh, Saudi Arabia. Materials and Methods: We retrospectively studied records of 720 patients with AF seen in outpatients and inpatients departments at King Abdulaziz Medical City, Riyadh, during the period of 1 January 2002 to 31 August 2008. Results: Documented acute and chronic AF was present in 157 (21.8%) and 563 (78.1%) patients, respectively. Palpitations, dizziness and syncope were the most frequent symptoms in acute AF, while dyspnea and palpitations were the most common symptoms in the chronic type. Acute respiratory problems and acute myocardial infarction were significantly more common in acute AF, while congestive heart failure and acute respiratory problems (chest infection, bronchial asthma, and pulmonary embolism) were significantly more common in chronic AF. The most common causes of both types of AF were diabetes mellitus (DM) in 68.8%, hypertension (HTN) in 59.3%, chronic lung diseases (bronchial asthma, chronic obstructive pulmonary disease and interstitial lung disease) in 31.8%, valvular heart disease in 23.6%, and ischemic heart disease (IHD) in 23.1%. In 9 (1.3%) patients, no cause was detected. The echocardiographic findings of left ventricular hypertrophy, valve lesions, and depressed left ventricular function were significantly more common in chronic AF (P<0.01). Conclusions : Nowadays, DM, HTN, and IHD are becoming the most common predisposing factors for AF in the central region of Saudi Arabia and require prevention and control